Analysis of the Meaning of the Word Sayyid In the Qur'an and al-Hadis - Dame Siregar; Agus Anwar Pahutar (Institut Agama Islam Negeri Padangsidimpuan, 2022)
There should be a valid argument for worship before it can be practiced. If it is not obligatory to leave it, it is enough and complete the Qur'an and hadith, why are you still looking for a rational argument that contradicts the naql argument. There are 3 meanings of sayyid in the Qur'an, namely follower, husband and leader. Sayyid ah is termed in Indonesia as (siti) is the wife, there is a queen in heaven, if a man is called the king (the term local adat title, meaning it is permissible to call kiyai, Buyya, ustad, Baleo and others, it means that academic degrees such as Dr, Ph.D, may hold positions such as president, may title abri such as generals. The meaning of sayid is lower than the name given by Allah, namely Muhammad, Ahmad, 'Abdun Rosul Nabi and ummi. The use of the word sayyid or sayyid ah in worship has not found the evidence. If it is better, add the word Of course the monotheism sentence becomes: لااله الا الله سيدنا محمد رسول الله, it is also possible to pronounce the shahada to Muhammad as: وأشهد أن سيدنا محمدا عبده ورسوله, and the reading in the adhan iqamah and others, may also be the name of the surah سيدنا محمد and every word added with the word Muhammad سيدنا